Extending the Minority Stress Model to Incorporate HIV-Positive Gay and Bisexual Men's Experiences: a Longitudinal Examination of Mental Health and Sexual Risk Behavior. - Rendina, H Jonathon; Gamarel, Kristi E; Pachankis, John E; Ventuneac, Ana; Grov, Christian; Parsons, Jeffrey T (Annals of behavioral medicine : a publication of the Society of Behavioral Medicine, 2016)
Minority stress theory represents the most plausible conceptual framework for explaining health disparities for gay and bisexual men (GBM). However, little focus has been given to including the unique stressors experienced by HIV-positive GBM.